Productivity, profitability and nutrient uptake in carrot (Daucus carota) and radish (Raphanus sativus) crops under sulphur nutrition - SINGH, DINESH PRATAP; SINGH, HARVENDRA; ALI, JAVED; SINGH, S P (The Indian Journal of Agricultural Sciences, 2016)
A field experiment was conducted during winter (rabi) seasons of 2009-10 and 2010-11 to study the response of sulphur fertilization on carrot (Daucus carota L.) and radish (Raphanus sativus L.) on alluvial soil at Bichpuri, Agra (Uttar Pradesh). The treatments comprised five levels of sulphur (0, 15, 30, 45 and 60 kg/ha) were evaluated in randomized block design with four replications. The results revealed that the application of sulphur up to 30 and 45 kg/ha significantly increased the edible root yields and dry matter production of carrot and radish, respectively. The magnitude of mean response to sulphur application differed from crop to crop and was recorded as carrot (17.5%) and adish (18.6%) over control. Successive sulphur levels had a significant effect on its uptake by both the vegetable crops up to 60 kg S/ha. A phenomenal increase in N, P and K uptake, except of Zn was recorded in these crops due to increasing levels of S up to 60 kg/ha. The maximum removal of N, P, K and S was recorded with radish roots while that of Zn with carrot. The higher amounts of protein and protein yield were recorded in carrot followed by radish. Sulphur application significantly improved the content and yield of protein in these vegetable crops over control and maximum values were recorded at 60 kg S/ha. Carrot gave maximum net returns ₹ 137 665/ha and B:C ratio (2.51) with 45 kg S/ha. However, the net returns (₹ 65 640/ha) and B:C ratio (1.57) were the highest in radish with 60 kg S/ha. The apparent recovery of sulphur was influenced by S levels with maximum at 30 kg S/ha in carrot and radish. Better sulphur use efficiency in carrot (179.5 kg produce kg/S applied) and radish (186.1 kg produce kg/S applied) was obtained with 30 kg S/ha. The sulphur use efficiency decreased with its increasing levels and minimum use efficiency was recorded with 60 kg S/ha application.